Functional & Radiological Outcomes of Suprapatellar Intramedullary Nailing in Proximal Tibial & Tibial Shaft Fractures: A Prospective Study (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Proximal tibial and tibial shaft fractures are common injuries often caused by high-energy trauma. Conventional infrapatellar intramedullary nailing with the knee in flexion may lead to difficulty in maintaining alignment, whereas the suprapatellar semi-extended approach improves fracture reduction, alignment control, and surgical ergonomics.Aim & Objectives: To evaluate the effectiveness of suprapatellar intramedullary nailing in proximal tibial and tibial shaft fractures by assessing fracture reduction, alignment, functional and radiological outcomes, and postoperative complications associated with the suprapatellar approach. Materials & Methods: A prospective observational study was conducted on 30 patients with proximal tibial and tibial shaft fractures treated with suprapatellar intramedullary nailing at Kanti Devi Medical College Hospital & Research Centre. Patients were followed for six months with clinical and radiological evaluation. Functional outcomes were assessed using the Lysholm Knee Scoring Scale and LEFS, while arthroscopy was used to evaluate patellofemoral cartilage integrity before and after nail insertion.Results: The mean age of patients was 48.2 ± 18.6 years. Radiological union was achieved within 16 weeks in 86.6% of patients, with a mean union time of 13.8 ± 2.7 weeks. Knee flexion greater than 120° was achieved in 66.7% of patients. The mean Lysholm score was 82.6 ± 11.4 and the mean LEFS score was 69.2 ± 12.1. Anterior knee pain was observed in 6.6% of patients. Arthroscopic evaluation demonstrated minimal patellofemoral cartilage injury in most cases.Conclusions: Suprapatellar intramedullary nailing is a safe and effective technique for proximal tibial and tibial shaft fractures. The semi-extended position facilitates improved fracture alignment and provides satisfactory fracture union with good functional outcomes and minimal complications.